Synthesis of 1,2-Fused Bicyclic Imidazolidin-4-ones by Redox-Neutral Cyclization Reaction of Cyclic Amines and α-Ketoamides - Liu, Yi; Wu, Jiashou; Jin, Zhengneng; Jiang, Huajiang (Synlett, 2018)
A redox annulation reaction of cyclic amines and α-ketoamides was developed. A variety of 1,2-fused bicyclic imidazolidin-4-ones were synthesized in moderate to good yields from cyclic amines by redox-neutral α-C–H functionalization.
Keywords: redox annulation; cyclic amine; α-ketoamide; bicyclic imidazolidin-4-one; α-C–H functionalization